Church space and the capital in prewar Japan - Washington, Garrett L. (University of Hawaiʻi Press, 2022)
Christians have never even constituted one percent of Japan's population, yet Christianity had a disproportionately large influence on Japan's social, intellectual, and political development. This happened despite the Tokugawa shogunate's successful efforts to criminalize Christianity and even after the Meiji government took measures to limit its influence (after decriminalizing it out of diplomatic necessity). From journalism and literature, to medicine, education, and politics, the mark of Protestant Japanese is indelible. Herein lies the conundrum that has interested scholars for decades. How did Christianity overcome the ideological legacies of its past in Japan? How did Protestantism distinguish itself from the other options in the religious landscape like Buddhism and New Religions? And how did the religious movement's social relevance and activism persist despite the new government's measures to weaken the relationship between private religion and secular social life in Japan?In Church Space and the Capital in Prewar Japan, Garrett Washington responds to these questions with a spatially explicit study on the influence of the Protestant church in imperial Japan. He examines the physical and social spaces that Tokyo's largest Japanese-led Protestant congregations cultivated between 1879 and 1923 and their broader social ties. These churches developed alongside, and competed with, the locational, architectural, and social spaces of Buddhism, Shinto, and Japanese New Religions. Their success depended on their pastors' decisions about location and relocation, those men's conceptualizations of the new imperial capital and aspirations for Japan, and the Western-style buildings they commissioned. Japanese pastors and laypersons grappled with Christianity's relationships to national identity, political ideology, women's rights, Japanese imperialism, and modernity; church-based group activities aimed to raise social awareness and improve society. Further, it was largely through attendees' externalized ideals, experiences, and networks developed at church but expressed in their public lives outside the church that Protestant Christianity exerted such a visible, surprising influence on modern Japanese society. This groundbreaking history offers answers to longstanding questions about Protestant Christianity's reputation and impact, but also goes further. It importantly uses a new space-centered perspective to focus attention on Japanese agency in the religion's metamorphosis and social impact, adding a fresh narrative of cultural imperialism.